A Literature Review: Which Regulation is Feasible for Assessing User Satisfaction with Terminal Services? - Agung Riyardi; Mohd Fahmy-Abdullah; Sujadi Sujadi; Kusdiyanto Kusdiyanto; Triyono Triyono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Three different studies have discussed regulations ofthe assessment of user satisfaction levelswith terminal services. Based on the assumption that the terminal attributes derived from regulations are accurate, this study aims to analyze the content of the regulations, compare them, and analyzeterminal user satisfaction as assessed by previous studies. Content analysis of the literature is conducted. The results reveal that among the user satisfaction survey regulations from the Minister of Administrative and Bureaucratic Reform Regulations of 16/2014 and 25/2004 and the service standard regulations from the Minister of Transportation Regulation of 40/2015, the most feasible regulation for the assessment of user satisfaction is the Minister of Transportation Regulation of 40/2015. This regulation does not regulate satisfaction assessment but can be used as a basis for assessments of user satisfaction with terminal services. All of the stipulated service standards can be classified as accurate terminal service attributes. Therefore, improvements can be made by including a requirement for satisfaction assessments. Through the incorporation of the service quality concept, such improvement could establish this regulation as a basis for reputable studies of satisfaction assessments. Another result reveals that the literature on the assessment of terminal user satisfaction based on the Minister of Transportation Regulation of 40/2015 reports that users are satisfiedwith the terminal attributes of reliability, convenience, affordability and equity, but they are unsatisfied with the attributes ofsafety and security. Thus,terminals should implement maximal regulation of service standards. Assurance of terminal securitycould increase user satisfaction.